Afro-Nostalgia : Feeling Good in Contemporary Black Culture - Ahad-Legardy, Badia, 1974- (Book collections on Project MUSE., 2021)
"African descent could not experience nostalgia. As a result, black lives have been predominately narrated through historical scenes of slavery and oppression. This phenomenon created a missing archive of romantic historical memories. Badia Ahad-Legardy mines literature, visual culture, performance, and culinary arts to form an archive of black historical joy for use by the African-descended. Her analysis reveals how contemporary black artists find more than trauma and subjugation within the historical past. Drawing on contemporary African American culture and recent psychological studies, Ahad-Legardy reveals nostalgia's capacity to produce positive emotions. Afro-nostalgia emerges as an expression of black romantic recollection that creates and inspires good feelings even within our darkest moments"--